Diseño e Implementación De Un Sistema De Costos Por Ordenes Para La Empresa Golosinas Helados & Amasijos Belén S.A.S (2021)
This research was carried out in order to design and implement a costing system that allows to know the reality of production costs, to know the management and distribution of manufacturing costs to microenterprises engaged in the production and marketing of perishable and frozen products in a traditional or handmade way. The realization of this project will allow to identify and measure the three main elements of the cost such as: raw material, labor and indirect manufacturing costs used to obtain a product, as well as it will facilitate the managers of the organization to carry out a planning that allows to measure and establish the objectives that facilitate the decision making in front of the management and purchase of raw materials, storage and control of finished product. The calculation of costs is essential for the planning of products as well as for the determination of sales prices and inventory control, so the organization will have adequate tools to compete healthily in the market and have a growth over time.